Electrical Density Gauge, A Device for Quick Quality Control of Soil Compaction Case Study in Indonesia - Purwana, Yusep Muslih; Setiawan, Bambang; Warman, Mutiar; Rifai, Muchamad; Suryaningtyas, Indah (International Journal of Sustainable Construction Engineering and Technology, 2025)
Soil compaction can be a main civil works such as road embankment, earth fill dam, airport, etc. During construction, soil is compacted layer by layer and the quality of each layer is controlled by a ratio between its dry density and the maximum dry density obtained from a Proctor test. In the field, the test is immediately conducted after compaction by measuring the moisture content and unit weight of soil. A very common conventional method of this measurement is sand cone or rubber balloon method, and of course it can be a constraint for a rapid project. Recently, a complex impedance measuring instrument (CIMI) method, commonly known as electrical density gauge (EDG) is introduced in Indonesia. It is a quick method to control the compaction quality simply by giving a DC electric current through a particular soil layer, and the result is obtained immediately within a few minutes. EDG must be calibrated by generating a soil model, simply by inputting a series of physical-electrical properties of a soil. Once calibration is completed, physical properties of soil in the field can be predicted simply by giving electric current on it. Although this method has been utilized in many countries, it has not been used in Indonesia. The aim of this study is to investigate the performance of EDG and its possible widely use in Indonesia. Three different soils from different quarries were investigated. Soils with different moisture content were compacted with different energy into 40 cm in diameter and 30 cm in height of concrete molds as modification of Proctor mold. 15 tests have been conducted to compare the result from EDG and sand cone methods. The analysis was conducted statistically using main absolute error (MAE) and determination coefficient (R2). The result indicates that EDG shows a good performance for measuring soil moisture content and density.